Prognostic Value of Radiological Extranodal Extension Detected by Computed Tomography for Predicting Outcomes in Patients With Locally Advanced Head and Neck Squamous Cell Cancer Treated With Radical Concurrent Chemoradiotherapy - Mahajan, Abhishek; Chand, Ankur; Agarwal, Ujjwal; Patil, Vijay; Vaish, Richa; Noronha, Vanita; Joshi, Amit; Kapoor, Akhil; Sable, Nilesh; Ahuja, Ankita; Shukla, Shreya; Menon, Nandini; et al. (Frontiers in Oncology, 2022)
Objective: ENE assessment in LAHNSCC treated with CCRT is challenging and hence the AJCC N staging. We hypothesized that rENE may directly impact outcomes in LAHNSCC treated with radical CCRT. Materials and methods: Open-label, investigator-initiated, randomized controlled trial (2012-2018) which included LAHNSCC planned for CCRT. Patients were randomized 1:1 to radical radiotherapy (66-70 grays) with concurrent weekly cisplatin (30 mg/m2) (cisplatin radiation arm - CRT) or same schedule of CRT with weekly nimotuzumab (200 mg) (nimotuzumab plus cisplatin radiation arm- NCRT). 536 patients were accrued,182 were excluded due to the non-availability of Digital Imaging and communications in Medicine (DICOM) CT data. 354 patients were analyzed for rENE. Metastatic nodes were evaluated based on 5 criteria and further classified as rENE positive/negative based on 3 criteria. We evaluated the association of rENE and disease-free survival (DFS), loco-regional recurrence-free survival (LRRFS), and overall survival (OS). Results: 244(68.9%) patients had radiologically metastatic nodes (rN), out of which 140(57.3%) had rENE. No significant association was found between rENE and CRT or NCRT (p-value 0.412) arm. The median follow-up period was 39 months (95%CI 35.5 to 42.8 months). Complete response (CR) was seen in 204 (57.6%), Incomplete response (IR) i.e. partial response plus stable disease (PR+SD) in 126(35.6%) and progressive disease (PD) in 24(6.8%). rENE positive had poor 3-year OS (46.7%), poor DFS (48.8%) and LRRFS (39.9%) than rENE negative (63.6%, 87%, 60.4%). rENE positive had 1.71 times increased risk of IR than rENE negative. Overall stage, site, clinical positive node (cN), response, rENE were the only significant factors for predicting OS, DFS and LRRFS. Conclusion: Pre-treatment rENE is an independent prognostic marker for survival (OS, DFS, LRRFS) in patients with LAHNSCC treated radically with CCRT and can be used as a predictive marker to stratify patients into responders vs non-responders. We have proposed the Mahajan et. al. imaging-based ENE (rENE) grading system which will be applicable on CT, MRI, PET-CECT and Ultrasound.